Recommendations for Pipes Selections in Heating and Cooling Systems - Cătălin Popovici; Jan Ignat (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section, 2009)
The present study finds it’s purpose in stressing that pipes selection is not just a matter of „how it is used”, or „how much does it costs” but also a question of „where” . Using experience of other countries, the work has at the basis calculation values from France, USA and UK and recommends selection tables of pipes diameters for low, medium and high pressure drops. Also, it illustrates the diameter choice in two different situations based on the economic criteria.